Kaligrafi Antidisonansi Emosi: Pelatihan Seni Kaligrafi sebagai Solusi Problematika Psikologis dan Sosial Anak di SDN Babalan Kidul - Fuad, Asfal; Sulaiman, M. Andi; Setianto, Gigih; Yulita, Dian; Rosanti, Cholisa (CV Global Research Publication, 2025)
The educational landscape at Babalan Kidul Elementary School reveals a problematic reality where children from disharmonious families experience emotional dissonance and psychological issues such as anxiety and low self-esteem. The program is geared towards developing self-resilience, enhancing self-concept, and providing sustainable social and economic skills. We applied a qualitative approach with a descriptive methodology. The program strategy integrates Art Therapy and Community Development through five stages: Initiating the Heart (observation and personal approach), Painting Emotions (project-based learning and expressive therapy), Self-Transformation (focus group discussion and reflection), Carving Achievements (MAPSI Competition preparation), and Sustainable Empowerment (art exhibition and economic workshops). The program successfully demonstrated the effectiveness of calligraphy as a non-verbal therapeutic medium, helping children channel negative emotions and foster inner peace. Furthermore, the program laid a foundation for sustainable empowerment by introducing the economic value of calligraphy, equipping children with essential social and economic skills.